ROSMARINIC ACID AND ITS PLANT SOURCES IN THE CRIMEA - A. E. Paliy; F. M. Melikov; O. A. Grebennikova; V. D. Rabotyagov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article presents data on the content of phenolics and rosmarinic acid in 32 species of aromatic and medicinal plants from Lamiaceae, Asteraceae and Apiaceae families, native to the South Coast of the Crimea. The concentration of phenolic compounds in the studied species was 490.3 - 18511.0 mg/100g of plant raw materials. Rosmarinic acid was found in 15 species from Lamiaceae and Asteraceae families. Rosmarinic acid was not noticed in the studied plants from Apiaceae family. The concentration of rosmarinic acid in the studied plants amounted to 40.6 - 2535.5 mg/100g of plant raw materials. On the basis of the obtained results such species as Origanum vulgare L., Majorana hortensis Moench., Mentha longifolia L., Thymus vulgaris L. (thymol type) can be considered as a promising source of rosmarinic acid.